OMIP 077: Definition of all principal human leukocyte populations using a broadly applicable 14‐color panel. Issue 1 (14th July 2021) - Boesch, Maximilian; Sykora, Martina; Gasteiger, Silvia; Baty, Florent; Brutsche, Martin H.; Sopper, Sieghart
Abstract: This Optimized Multicolor Immunofluorescence Panel was designed to identify and quantify all principal leukocyte populations in human blood using a minimum number of markers. We achieved this goal using a carefully selected combination of 14 surface markers compatible with standard flow cytometric instruments and accessible to a particularly large research community. Optimized for use in whole blood, this panel allows polymorphonuclear cell identification, supports live cell recovery, and is well‐suited for absolute cell counting applications in the original in vivo volume. Panel performance and the separation of populations are high, and virtually no cells remain undefined after gating. Besides the identification of neutrophils, eosinophils, basophils, T cells, natural killer cells, B cells, plasma cells, monocytes, myeloid dendritic cells and plasmacytoid dendritic cells, this panel also covers progenitor cells and may therefore be attractive for stem cell researchers. Envisioned applications of this panel include immune monitoring within clinical trials, initial discovery to inform subset‐targeted panels, and clinical diagnostics. In summary, this panel offers a broadly applicable platform for immune cell identification, quantification and characterization in human samples, particularly whole blood.